Evaluation of Telemedicine Experience: Artificial Intelligence in Cancer Care - A. A. Kostin; Yu. V. Samsonov (Здоровье мегаполиса)
Background. To date, one of the key tasks of our time, which has yet to be solved, is to provide medical services remotely using constantly advancing information and communication technologies. It is medical sciences that urgently needs ICT tools for various scopes: providing medical care in remote regions, organizing continuous education of medical personnel, managing electronic patient records, implementing mobile diagnostic devices, and managing network of branches or medical facilities at the institutional level. Telemedicine is a necessity, especially for patients with comorbid chronic diseases like cancer.Objective. To evaluate utilization of digital technologies at various stages of cancer care, through the example of artificial intelligence.Materials and methods. A systematic literature review was conducted using PRISMA. The search was carried out in such databases as Elibrary, PubMed, MEDLINE, Google Scholar by keywords “Telemedicine in oncology”, “COVID-19 in oncology”, “Artificial Intelligence”, “Digital Technologies”, “Data Personalization”, and “Teleoncology”. Publications not primarily focused on evaluating telemedicine technologies in oncology were excluded from the review process.Results. The literature review was conducted to consider the rapid integration of telemedicine since the pandemic, the risks associated with the widespread use of telemedicine in oncology, and the use of artificial intelligence in oncology, including the early detection and diagnosis of cancer. In conclusion, it is noted that the digitalization of healthcare radically changes the clinical workflow by expanding the possibilities for obtaining information from both medical staff and patients. Experience-based medicine is being replaced by an evidence-based, patient-centered approach. The rapidly developing artificial intelligence technologies will continue to have a great impact on the oncology in the near future. Both medical staff and scientific community must be prepared for the coming changes.